The Effect of Servicescape and Brand Image on Repurchase Intention Through Customer Satisfaction on Maxx Coffee Customers - Riki Thomas Tarigan; Beby Karina Fawzeea Sembiring; Syafrizal Helmi Situmorang (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this study was to determine and analyze the direct influence of Servicescape, Brand Image and Customer Satisfaction on Repurchase Intention and to see the role of Customer Satisfaction as an intervening variable. The research method used is descriptive associative using a sample of 150 respondents. The data analysis method used is (Partial Least Square) PLS using the Smart PLS application. The results showed that Servicescape and Customer Satisfaction have a positive and significant effect on Repurchase Intention; Brand Image has a positive but not significant effect on Repurchase Intention; Servicescape and Brand Image have a positive and significant effect on Customer Satisfaction; Servicescape and Brand Image have a positive and significant effect on Repurchase intention through customer satisfaction at Customer Maxx Coffee in Medan.